SOME METHODS FOR SAVING HEAT ENERGY WHILE MANUFACTURING VERTICAL INSULATING GLASS UNITS - S. A. Shybeka (Наука и техника)
The paper proposes and considers two constructive methods for saving heat energy while manufacturing vertical insulating glass units with various gas filling of inter-glass space. The first method presupposes manufacturing of insulating glass units having specific thickness which is calculated in accordance with specific features of convective heat exchange in the closed loop circuit. Value of the heat-exchange coefficient depends on gas properties which is filling a chamber capacity (coefficients of thermal conductivity, volumetric expansion, kinematic viscosity, thermometric conducivity), temperature difference on the boundary of interlayer and its thickness. It has been shown that while increasing thickness of gas layer convective heat exchange coefficient is initially decreasing up to specific value and then after insignificant increase it practically remains constant. In this connection optimum thicknesses of filled inter-layers for widely-spread gas in production (dry air, argon, krypton, xenon) and for carbon dioxide have determined in the paper. Manufacturing of insulating glass units with large thickness of gas chamber practically does not lead to an increase in resistance to heat transfer but it will increase gas consumption rate. The second industrial economic method is interrelated with application of carbon dioxide СО2 as a filler of inter-glass space which has some advantages in comparison with other gases (small cost due to abundance, nontoxicity, transparency for visual light and absorption of heat rays). Calculations have shown that application of carbon dioxide will make it possible to increase resistance to heat transfer of one-chamber glass unit by 0.05 m²×K/W (with emissivity factor of internal glass – 0.837) or by 0.16 m²×K/W (with emission factor – 0.1) in comparison with the glass unit where a chamber is filled with dry air.